Unraveling the isomeric heterogeneity of glycans: ion mobility separations in structures for lossless ion manipulations. Issue 83 (28th September 2018) - Nagy, Gabe; Attah, Isaac K.; Garimella, Sandilya V. B.; Tang, Keqi; Ibrahim, Yehia M.; Baker, Erin S.; Smith, Richard D.
Abstract : A new ultrahigh resolution ion mobility platform enables the fast separation and characterization of isomeric glycoforms. Abstract : To address the challenges associated with glycan analyses, we have implemented a structures for lossless ion manipulations (SLIM) serpentine ultra-long path with extended routing (SUPER) ion mobility-mass spectrometry ( i.e. SLIM SUPER IM-MS) platform to achieve much higher resolution of isomeric glycoforms. We have demonstrated the potential of this platform as a future component of the glycomics toolbox.